The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1158/0008-5472.can-06-2366
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of MDS1/EVI1 and EVI1, Located in the 3q26.2 Amplicon, Is Associated with Favorable Patient Prognosis in Ovarian Cancer

Abstract: Increased copy number involving chromosome 3q26 is a frequent and early event in cancers of the ovary, lung, head and neck, cervix, and BRCA1 positive and basal breast cancers. The p110A catalytic subunit of phosphoinositide-3-kinase (PI3KCA) and protein kinase CI (PKCI) have previously been shown as functionally deregulated by 3q copy number increase. High-resolution array comparative genomic hybridization of 235 high-grade serous epithelial ovarian cancers using contiguous bacterial artificial chromosomes ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
147
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(162 citation statements)
references
References 43 publications
14
147
1
Order By: Relevance
“…4C), consistent with EVI1's known function as a critical regulator of embryonic development (12,32). We also found marked enrichment for genes controlling processes formerly associated with EVI1 (10,12,33), including apoptosis, cell proliferation, and migration. Interestingly, several potential biological functions were associated with EVI1 target genes, including cell adhesion, cell metabolism, response to oxidative stress, cell structure, and motility.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…4C), consistent with EVI1's known function as a critical regulator of embryonic development (12,32). We also found marked enrichment for genes controlling processes formerly associated with EVI1 (10,12,33), including apoptosis, cell proliferation, and migration. Interestingly, several potential biological functions were associated with EVI1 target genes, including cell adhesion, cell metabolism, response to oxidative stress, cell structure, and motility.…”
Section: Resultssupporting
confidence: 80%
“…Collectively, our data indicate that EVI1 is a multipurpose transcription factor that synergizes with FOS in invasive tumors. E cotropic viral integration site 1 (EVI1) is a zinc finger (ZNF) transcription factor (TF), and its overexpression in myeloid leukemia (1)(2)(3) and epithelial cancers (1,2,(4)(5)(6)(7)(8)(9) has been extensively studied and correlated with adverse patient outcome (7,10,11). EVI1 also controls several aspects of embryonic development, including hematopoiesis, angiogenesis, and heart and neural development (12).…”
mentioning
confidence: 99%
“…Several reports in the literature lend support to the thesis of ''multiple driver genes'' per amplicon. Amplicons that have been shown functionally involving multiple driver genes include the 11q22 amplicon in liver cancer (40), the HER2 amplicon (41), and the 8p11-12 amplicon (42) in breast cancer, the 3q26.2 amplicon in ovarian cancer (43), and finally the 19q13 amplicon in pancreatic cancer (44). Based on our findings, the focal point of this study, 14q13.3 amplicon, is very likely to also involve multiple coamplified driver genes.…”
Section: Discussionmentioning
confidence: 61%
“…Many studies have demonstrated the significance of the cytoplasmic membranous expression of CD24 in the prediction of the prognosis of ovarian cancer patients (31)(32)(33)(34)(35). Protein levels of EVI1 and MDS1 were reported to be increased in both ovarian cancer tissues and ovarian cancer cell lines (36). Nanjundan et al (36) recently revealed that DNA copy number increases of both genes were associated with at least 5-fold-increased RNA transcript levels in 83 and 98% of advanced ovarian cancer cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Protein levels of EVI1 and MDS1 were reported to be increased in both ovarian cancer tissues and ovarian cancer cell lines (36). Nanjundan et al (36) recently revealed that DNA copy number increases of both genes were associated with at least 5-fold-increased RNA transcript levels in 83 and 98% of advanced ovarian cancer cases, respectively. The high expression level of homeobox member gene HOXB7 mRNA reveals its possible involvement in the invasive characteristics of ovarian cancer cells (37,38).…”
Section: Discussionmentioning
confidence: 99%